Preparation For The Implementation Of The Independent Curriculum - Ibrahim, Ibrahim; Husnah, Azimmatul; Fadillah, Alya Rasiqha; Eriska, Eriska; Amanda, Suci (Journal Analytica Islamica, 2024)
This article relates to the preparation for the implementation of the Merdeka curriculum at SDN 158 Palembang. The research type is qualitative with a descriptive approach. Data collection methods include interviews, observations, and documentary studies. The data analysis technique involves stages of data collection, data presentation, verification, and drawing conclusions. The validity of the data is examined through triangulation consisting of time, method, and source triangulation. Based on the results and discussions, the preparation for the implementation of the Merdeka Curriculum at SDN 158 Palembang indicates that the school has prepared itself to implement the curriculum in accordance with government regulations. The preparation involves understanding and readiness related to the implementation of the Merdeka Curriculum. Educators undergo education and training to understand and be familiar with the preparation and implementation processes of the Merdeka Curriculum. The implementation of the Merdeka Curriculum is considered an initiative that provides more creativity and flexibility to teachers and schools in designing and implementing the curriculum. Several preparation steps have been taken, including understanding the concept of the Merdeka Curriculum, identifying potential and needs involving all stakeholders, training for teachers, adjusting learning programs, as well as curriculum planning and development. These preparation stages are designed to assist educators and educational units in setting goals for the implementation of the Merdeka Curriculum. The readiness of each educator and educational unit can vary, so these implementation stages are designed so that each educator can confidently try to apply the Merdeka Curriculum. This confidence refers to the belief that educators have the ability to continue learning and improve their skills, not only in implementing the curriculum but also in the overall education process. The ability to continue learning is considered a crucial asset for educators.Artikel ini berkaitan dengan persiapan implementasi kurikulum Merdeka di SDN 158 Palembang. Jenis penelitian adalah kualitatif dengan pendekatan desktiptif. Metode pengumpulan data melalui wawancara, observasi dan studi dokumentasi. Teknik analisis data melalui tahapan pengumpulan data, penyajian data, verifikasi dan penarikan kesimpulan. Teknik pemeriksaan keabsahan data mmelalui triangulasi yang terdiri dari triangulasi waktu, metode dan sumber. Berdasarkan hasil dan pembahasan bahwa persiapan implementasi Kurikulum Merdeka di SDN 158 Palembang menunjukkan bahwa sekolah telah mempersiapkan diri untuk menjalankan kurikulum tersebut sesuai dengan regulasi pemerintah. Persiapan melibatkan pemahaman dan kesiapan terkait implementasi Kurikulum Merdeka. Tenaga pendidik menjalani pendidikan dan pelatihan untuk memahami serta mengenal proses persiapan dan pelaksanaan Kurikulum Merdeka. Penerapan Kurikulum Merdeka dianggap sebagai inisiatif yang memberikan lebih banyak kreativitas dan fleksibilitas kepada guru dan sekolah dalam merancang serta melaksanakan kurikulum. Beberapa langkah persiapan telah dilakukan, termasuk pemahaman konsep Kurikulum Merdeka, identifikasi potensi dan kebutuhan dengan melibatkan semua stakeholder, pelatihan bagi guru, penyesuaian program pembelajaran, serta perencanaan dan pengembangan kurikulum. Tahapan persiapan ini didesain untuk membantu pendidik dan satuan pendidikan menetapkan tujuan implementasi Kurikulum Merdeka. Kesiapan setiap pendidik dan satuan pendidikan dapat beragam, sehingga tahapan implementasi ini dirancang agar setiap pendidik dapat dengan percaya diri mencoba menerapkan Kurikulum Merdeka. Keyakinan ini merujuk pada pandangan bahwa pendidik memiliki kemampuan untuk terus belajar dan meningkatkan keterampilan mereka, tidak hanya dalam penerapan kurikulum, tetapi juga dalam proses pendidikan secara keseluruhan. Kemampuan untuk terus belajar dianggap sebagai modal penting bagi pendidik.